Supportive supervision for medicines management in government health facilities in Kiambu County, Kenya: a health workers’ perspective - Agoro, Oscar Otieno (Pan Afr Med J, 2015)
INTRODUCTION: Effective supportive supervision is widely recognized as essential for optimal management of medicines in government health facilities and also in contributing towards improved access and utilization of health services. This study sought to examine the extent supportive supervision for medicines management in government health facilities from a health worker perspective. METHODS: A cross-sectional study was done targeting health workers managing medicines in government health facilities in Kiambu County. One hundred and thirty eight respondents took part in the study which explored the quality of supportive supervision from a health worker's perspective, and also examined the factors influencing their contentment with the level of supervision received. A statistical analysis was done using SPSS 21 and Excel 2013. RESULTS: Supervisory visits from all levels of health management were not regularly done, standard checklists were not routinely used, and action plans irregularly developed and followed up. Only 54 (38.6%) respondents were satisfied with the levels of supportive supervision that they received, with satisfaction significantly differing across the professional cadres, χ(2) (12, n = 138) = 29.762, p = .003; across the different tiers of health facilities, r(s) (138) = 0.341, p < .001; and with the education levels of the respondents, r(s) (138) = 0.381, p < .001. CONCLUSION: The study concluded that supportive supervision for medicines management that government health facilities received was still inadequate, and health workers were dissatisfied with the level of supervision that they received. The study recommends a review of the support supervision policy at the county level to address the unearthed inefficiencies and improve supervision for medicines management in government health facilities.